A qualitative investigation of facilitators and barriers to accessing COVID-19 vaccines among Racialized and Indigenous Peoples in Canada. Issue 6 (30th November 2022) - Aylsworth, Laura; Manca, Terra; Dubé, Ève; Labbé, Fabienne; Driedger, S. Michelle; Benzies, Karen; MacDonald, Noni; Graham, Janice; MacDonald, Shannon E.
ABSTRACT: Structural and systemic inequalities can contribute to susceptibility to COVID-19 disease and limited access to vaccines. Recognizing that Racialized and Indigenous Peoples may experience unique barriers to COVID-19 vaccination, this study explored early COVID-19 vaccine accessibility, including barriers and potential solutions to vaccine access, for these communities in Canada. We conducted semi-structured interviews about challenges to accessing COVID-19 vaccination with Racialized and Indigenous Peoples, including linguistic minorities and newcomers, in Spring 2021, just as COVID-19 vaccines were becoming more widely available in Canada. Participants were purposely selected from respondents to a Canadian national online survey. Three researchers analyzed the interviews for emergent themes using a descriptive content analysis approach in NVivo. At the time of the interview, interview participants (N = 27) intended to receive (n = 15) or had received (n = 11) at least one vaccine dose, or did not state their status (n = 1). Participants described multiple barriers to COVID-19 vaccination that they personally experienced and/or anticipated they or others could experience – including technology requirements, language barriers, lack of identification documentation, and travel challenges – as well as related solutions. These were organized into three broad categories: 1) COVID-19 disease and vaccination information, 2) vaccination booking procedures, and 3) vaccination sites. These structural and systemic barriers during the initial months of vaccine rollout substantially restricted participants' COVID-19 vaccination access, even when they were eager to get vaccinated, and should be addressed early in vaccine rollouts to facilitate optimal uptake for everyone everywhere